Consensus on revised definitions of Morphological Uterus Sonographic Assessment (MUSA) features of adenomyosis: results of modified Delphi procedure. (1st July 2022) - Harmsen, M. J.; Van den Bosch, T.; de Leeuw, R. A.; Dueholm, M.; Exacoustos, C.; Valentin, L.; Hehenkamp, W. J. K.; Groenman, F.; De Bruyn, C.; Rasmussen, C.; Lazzeri, L.; Jokubkiene, L.; et al.
ABSTRACT: Objectives: To evaluate whether the Morphological Uterus Sonographic Assessment (MUSA) features of adenomyosis need to be better defined and, if deemed necessary, to reach consensus on the updated definitions. Methods: A modified Delphi procedure was performed among European gynecologists with expertise in ultrasound diagnosis of adenomyosis. To identify MUSA features that might need revision, 15 two‐dimensional (2D) video recordings (four recordings also included three‐dimensional (3D) still images) of transvaginal ultrasound (TVS) examinations of the uterus were presented in the first Delphi round (online questionnaire). Experts were asked to confirm or refute the presence of each of the nine MUSA features of adenomyosis (described in the original MUSA consensus statement) in each of the 15 videoclips and to provide comments. In the second Delphi round (online questionnaire), the results of the first round and suggestions for revision of MUSA features were shared with the experts before they were asked to assess a new set of 2D and 3D still images of TVS examinations and to provide feedback on the proposed revisions. A third Delphi round (virtual group meeting) was conducted to discuss and reach final consensus on revised definitions of MUSA features. Consensus was predefined as at least 66.7% agreement between experts. Results: Of 18 invited experts, 16 agreed to participate in the Delphi procedure. Eleven experts completed and four experts partly finished the first round. The experts identified a need for more detailed definitions of some MUSA features. They recommended use of 3D ultrasound to optimize visualization of the junctional zone. Fifteen experts participated in the second round and reached consensus on the presence or absence of ultrasound features of adenomyosis in most of the still images. Consensus was reached for all revised definitions except those for subendometrial lines and buds and interrupted junctional zone. Thirteen experts joined the online meeting, in which they discussed and agreed on final revisions of the MUSA definitions. There was consensus on the need to distinguish between direct features of adenomyosis, i.e. features indicating presence of ectopic endometrial tissue in the myometrium, and indirect features, i.e. features reflecting changes in the myometrium secondary to presence of endometrial tissue in the myometrium. Myometrial cysts, hyperechogenic islands and echogenic subendometrial lines and buds were classified unanimously as direct features of adenomyosis. Globular uterus, asymmetrical myometrial thickening, fan‐shaped shadowing, translesional vascularity, irregular junctional zone and interrupted junctional zone were classified as indirect features of adenomyosis. Conclusion: Consensus between gynecologists with expertise in ultrasound diagnosis of adenomyosis was achieved regarding revised definitions of the MUSA features of adenomyosis and on the classification of MUSA features as direct or indirect signs of adenomyosis. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Consenso sobre las definiciones revisadas de las características de la Evaluación Ecográfica de la Morfología del Útero (MUSA, por sus siglas en inglés) de la adenomiosis: resultados de un procedimiento Delphi modificado Objetivos: Evaluar si es necesario definir mejor las características de la Evaluación Ecográfica de la Morfología del Útero (MUSA) de la adenomiosis y, si fuera necesario, llegar a un consenso sobre las definiciones actualizadas . Métodos: Se aplicó un procedimiento Delphi modificado entre especialistas en ginecología de Europa con experiencia en el diagnóstico ecográfico de la adenomiosis. Para identificar las características de la MUSA que podrían necesitar revisión, en la primera ronda Delphi (cuestionario en línea) se presentaron 15 grabaciones de vídeo bidimensionales (2D), cuatro de las cuales incluían también fotografías tridimensionales (3D), de exámenes mediante ecografía transvaginal (ETV) del útero. Se pidió a los especialistas que confirmaran o refutaran la presencia de cada una de las nueve características de la MUSA de la adenomiosis (descritas en la declaración original de consenso de la MUSA) en cada uno de los 15 vídeos y que aportaran comentarios. En la segunda ronda Delphi (cuestionario en línea), se compartieron con los especialistas los resultados de la primera ronda y las sugerencias sobre la revisión de las características de la MUSA, antes de pedirles que evaluaran un nuevo grupo de imágenes fotográficas en 2D y 3D de los exámenes de ETV y que aportaran sus comentarios sobre las revisiones propuestas. Se llevó a cabo una tercera ronda Delphi (reunión virtual en grupo) para debatir y alcanzar un consenso final sobre las definiciones revisadas de las características de la MUSA. El consenso se había definido previamente como un acuerdo de al menos el 66, 7% entre los especialistas . Resultados: De los 18 especialistas invitados, 16 aceptaron participar en el procedimiento Delphi. Once especialistas completaron la primera ronda y cuatro parcialmente. Los especialistas identificaron la necesidad de definiciones más detalladas de algunas características de la MUSA . Se recomendó el uso de la ecografía 3D para optimizar la visualización de la zona de unión. En la segunda ronda participaron quince especialistas y llegaron a un consenso sobre la presencia o ausencia de características ecográficas de la adenomiosis en la mayoría de las imágenes fotográficas. Se llegó a un consenso para todas las definiciones revisadas, excepto para las líneas y brotes subendometriales y la zona de unión interrumpida. Trece especialistas participaron en la reunión en línea, en la que debatieron y acordaron las revisiones finales de las definiciones de la MUSA. Se llegó a un consenso sobre la necesidad de distinguir entre las características directas de la adenomiosis, es decir, las que señalan la presencia de tejido endometrial ectópico en el miometrio, y las características indirectas, es decir, las que reflejan cambios en el miometrio secundarios a la presencia de tejido endometrial en el miometrio. Los quistes miometriales, las islas hiperecogénicas y las líneas y brotes subendometriales ecogénicos se clasificaron unánimemente como características directas de la adenomiosis. El útero globular, el engrosamiento asimétrico del miometrio, el oscurecimiento en forma de abanico, la vascularidad translesional, la zona de unión irregular y la zona de unión interrumpida se clasificaron como características indirectas de la adenomiosis . Conclusión: Se llegó a un consenso entre ginecólogos con experiencia en el diagnóstico ecográfico de la adenomiosis con respecto a las definiciones revisadas de las características de la MUSA de la adenomiosis y a la clasificación de las características de la MUSA como indicios directos o indirectos de la adenomiosis . 摘要: 基于子宫腺肌症的形态学子宫超声评估(MUSA)特征达成修订定义共识:改良德尔菲法结果 目的: 评估子宫腺肌症的形态学子宫超声评估(MUSA)特征，确认是否需要修订其定义，若认为有必要修订，则就更新最新定义达成共识。 方法: 由专业的欧洲子宫腺肌症超声诊断妇科医生应用改良德尔菲法。为了确定可能需要修订的MUSA特征，在第一轮德尔菲法程序(在线问卷)中呈现15份经阴道超声(TVS)检查的二维(2D)视频记录(其中4份记录还包括三维(3D)静态影像)。我们要求专家组逐一确认或否认15份视频短片中是否存在子宫腺肌症的九个MUSA特征(根据原始MUSA共识声明中的描述)并发表意见。在第二轮德尔菲法程序(在线问卷)中向专家组通报第一轮的结果以及对MUSA特征的修订建议，然后要求他们评估一组新的TVS检查二维和三维静态图像，并且对拟采取的修订提供反馈。第三轮德尔菲法程序(虚拟小组会议)讨论MUSA特征的修订定义并达成最终共识。共识被预先定义为至少66.7%的专家取得一致意见。 结果: 我们邀请18位专家，其中16位同意参加德尔菲法程序。 11位专家完成第一轮，而4位专家部分完成第一轮。专家组认为需要对某些MUSA特征给出 更为详细的定义。他们建议通过三维超声优化交界区的可视化。15位专家参加第二轮并就多数静态影像中是否存在子宫腺肌症的超声特征达成共识。除了子宫内膜下线纹以及中断交界区的定义外，专家组就所有其他修订定义达成共识。13位专家参加在线会议，讨论并同意对MUSA定义的最终修订。专家组一致认为需要区分子宫腺肌症的直接特征(即表明子宫肌层存在异位子宫内膜组织的特征)和间接特征(即反映子宫肌层继发于子宫内膜组织的变化特征)。子宫肌层囊肿、高回声团以及子宫内膜下回声线纹被一致归为子宫腺肌症的直接特征。子宫呈球形，不对称的子宫肌层增厚，扇形阴影，跨病变血管分布，不规则交界区和中断交界区则被列为是子宫腺肌症的间接特征。 结论: 专业的子宫腺肌症超声诊断妇科医生在修订子宫腺肌症MUSA特征的定义以及MUSA特征作为子宫腺肌症的直接或间接标志的分类方面达成共识。